Енергетичний потенціал горючих вторинних енергоресурсів і водню, а також витрати на їх підготовку до прямого спалювання - Bilodid V.D.; Kuts G.O. (General Energy Institute of the National Academy of Sciences of Ukraine, 2011)
The levels of use of combustible secondary energy resources (CSER) and determined the direct costs of energy sources in their preparation for combustion in power plants. As of 2009, the total output of CSER was 9317.3 thousand the, from which the used 8059 (86.5 % of output), losses - 1258.3 (13.5). For certain types of CSER: losses are blast furnace gas - 450.5 thousand tons of standard fuel (7.58 % of total output), converter gas -397.7 (98.39), ferroalloy gas - 153.1 (66.42), waste from logging and wood processing – 28.5 (22.82), black liquor fully utilized.Direct costs of energy resources for the preparation of the above species of CSER are minor and are as follows: for the blast furnace gas - 3.77 kg of standard fuel/tce (blast furnace gas is given to the value of fuel through its heat of combustion), converter gas – 1.2 and ferroalloy – 1.64. Given the structural changes in production sources of CSER, assess their potential for possible use in the near future, whose value may be in the range 1.0 - 1,1 million tce.The article presents data on the costs of energy for hydrogen production using different technologies. These costs far exceed its energy potential. According to this analysis, the total costs of energy resources for 1 ton of hydrogen contained up to 1 ton of fuel equivalent are within 1.6-5.1 tce.